PERBANDINGAN PENDAPATAN PETANI PADI SAWAH BERDASARKAN ETNIS DAN STATUS PENGUASAAN LAHAN DI DUMOGA KABUPATEN BOLAANG MONGONDOW - Rifki Ferdinand Lalo; Mex Frans Lodwyk Sondakh; Sherly Gladys Jocom (AGRI-SOSIOEKONOMI, 2020)
The purpose of this study was to determine the comparison of the income of rice farmers based on: (1) land tenure status and (2) ethnicity in Dumoga Bolaang Mongondow Regency. Primary data collection in this study was in the form of data obtained from the results of direct interviews with farmers from each ethnic group of Bolaang-Mongondow, Minahasa, Bali and Java. Secondary data were obtained from documents from related institutions and journal articles and documents from libraries and the internet relating to the title of this study. Determination of the location of the study was done intentionally (purposive sampling) that is the area that is the center of the rice paddy plants. Sampling was done accidentally (accidently sampling) to the owner's farmers, tenant farmers, and tenant farmers based on land tenure and ethnicity status. Each ethnic of paddy rice farmers in the location was taken by 15 respondents so that the total number of respondents from all ethnic groups was 60 respondent farmers. The calculated variables are land area, total production, fixed costs and variable costs, revenue and income. To analyze the comparison of rice income based on ethnicity and land tenure status of rice farmers. Data analysis in the form of acceptance, income and descriptive analysis. The results showed the largest amount of income based on the status of land ownership owned by farmers in each ethnic owner. The biggest income based on ethnicity is owned by rice farmers who come from Ethnic Mongondow.*eprm*